Cortisol Level Related Glucose Intolerance in Adult with Obese Central - Nurzakiah Hasan; Veni Hadju; Nurhaedar Jafar; Ridwan Mochtar Thaha (Journal of Health Science and Prevention, 2019)
Obesity is associated with an increased risk of diseases, especially central obesity. Central obesity is a risk factor of glucose intolerance. Glucose intolerance is the beginning of diabetes mellitus. Many factors influence glucose intolerance. The aim of this study was to investigate the relationship between cortisol levels and some other factors related glucose intolerance. This study was a cross-sectional study from 12 high schools in Makassar. The analysis for this study was performed with 54 teachers. Characteristic samples, anthropometry, fasting blood glucose (FBG), cortisol were measured for all samples. Blood plasma glucose was measured from venous blood samples. Respondents were mostly female (85.2%), married (87%), bachelor’s degree (79,6%) and Buginesse (66.7%). The average age of respondents was 49.37 years. The results showed a significant relationship formula: between high cortisol levels in respondents who experienced glucose intolerance (p=0.043). Stress variables did not show a significant relationship, but the average score was higher in those who experienced glucose intolerance than those who had normal glucose. The frequency of consumption of carbohydrates, fats, proteins, and Body mass index (BMI) did not show a significant relationship with glucose intolerance. Cortisol levels are associated with glucose intolerance in adults with central obesity.